Supermassive black holes coalescence mediated by massive perturbers: implications for gravitational waves emission and nuclear cluster formation - Arca Sedda, Manuel; Berczik, Peter; Spurzem, Rainer (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. A large fraction of galactic nuclei is expected to host supermassive black hole binaries (BHB), likely formed during the early phase of galaxies asse
Gesehen am 15.02.2019
Advance access publication 2018 December 19